Voluntary Withdrawal and Its Effect on Criminal Liability - Saleh, Ahmad; Alfawaarah, Mohammed (Journal of Legal Sciences, 2026)
The legal consequences of abstaining from committing a crime, which amounts to complete exemption from punishment or its reduction, may not be limited to the original perpetrator only, but rather its impact extends to the accessory shareholder as well, as this study concluded that the voluntary withdrawal of the accessory shareholder prevents him from being held accountable. From the attempt, but not as a deterrent to punishment, but because this avoidance negates the criminal behavior itself due to the absence of the criminal intent of the accessory contributor at a stage prior to the completion of the behavior. The most important recommendations were represented by the necessity of the legislation under study to legislate and regulate withdrawal and effective participation and approve the provisions related to it in detail to fill the gap. The wide range between the actual application of this legal system and the legal systems.